Design Improvement For Replica Trophy Using Reverse Engineering And Cnc Machining - Foo, Mun Yee (Universiti Sains Malaysia, 2019)
Trophy represents of achievement or victory of a person or team from an event. Along with the technologies, the manufacturing of a trophy has become easier, faster and low cost needed to produce a part. Replica Trophy is a product that required to produce according to the theme of the event. Therefore, reverse engineering is the most suitable way which helps to accelerate the development a new product with using the existing object. This can reduce the time that needed to sketch or design a new product. With the help of 3D scanner can help to obtain the data of complex structure and reduce the time to measure the object. In this study, it is required to produce the replica trophy from the event of Hall of Fame USM (Sanggar Sanjung USM) which is an appreciation event of the USM staff. This project is to identify the existing type of product which relate to the theme of the event by using the knowledge of product design. The survey is conducted to the target market to analyze the customer response. Few concepts are generated for selection, the study regarding the ability and accuracy of the Next Engine 3D laser scanner need to be considered. The scanning result can improve by increasing the scanning speed and time to obtain a dense data of point of cloud. Surface reconstruction is undergone after obtaining the scan result. The CAD data required to optimize the dimension and positions of the object to the desired result. The design of the concept needs to include the design of the multiple usage of the replica trophy to increase the functionality of the trophy. The product concept will be fabricated by using CNC machining with the aid of CAM software. This approach could lead to shorter time-consuming as compared with applying forward engineering method.